STRENGTH-WEAKNESS-OPPROTUNITY-THREAT (SWOT) ANALYSIS TO ENHANCE PRODUCTIVITY OF BATIK INDUSTRY CENTRE IN EAST JAVA PROVINCE INDONESIA - Dewi, Ika Atsari; Wijana, Susinggih; Nurmansyah, M. Andhy; Setiawan, Romy; Rohmah, Wendra G.; Rahmah, Nur Lailatul; Sari, Rheysa Permata (Universitas Negeri Medan, 2017)
AbstractIt is acknowledged that the struggle faced by the batik industry, particularly in the Province of East Java, dealing with growth challenges caused by several factors: less attractive design, the conventional use of manual handling, and less governmental-institutional support. The purpose of thisstudy is to analyze the performance of centers of Batik industry in Sampang, Trenggalek and Tuban Regencies highlighting their related-production quality and quantity. The location selection of batik production centers is based on coordination with Department of Industry and Trade in each area. Data is collected through surveys and interviews. This study concludes several things. There are six production system elements analyzed in this research included technology (production capacity of batik), funding, raw material, human resources, marketing, and pattern design.Keywords: batik pattern, micro small medium entreprises, productivity